2016
DOI: 10.1177/1475725716643267
|View full text |Cite
|
Sign up to set email alerts
|

The Discursive Construction of Group Cohesion in Problem-based Learning Tutorials

Abstract: Gillian Hendry is a PhD researcher at the University of Strathclyde, whose research interests lie in the field of qualitative and social psychology. Her on-going PhD project is focused on investigating interaction in student groups; using discursive psychology to analyse how teasing is constructed as a pro-social act.Dr Sally Wiggins is a senior lecturer in psychology at the University of Strathclyde. Her research interests focus on discursive practices in everyday interaction, particularly on the social const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…For instance, rather than explicitly disagreeing with Paul, note how she engages with the PBL worksheet ("what do they say") as a prompt for their collaborative action (Day & Wagner, 2014); explored in more depth later in the analysis. Furthermore, upon Paul's continued justification of his stance ("not reacting at all", 10), Megan's use of humour ("never know with the gases£", line 11) deflects from their misaligned views, and whilst they do not reach agreement, Paul shares in this laughter (line 12) which lightens the potential seriousness of the situation (Hendry, Wiggins & Anderson, 2016).…”
Section: Invoking Physical Resourcesmentioning
confidence: 99%
“…For instance, rather than explicitly disagreeing with Paul, note how she engages with the PBL worksheet ("what do they say") as a prompt for their collaborative action (Day & Wagner, 2014); explored in more depth later in the analysis. Furthermore, upon Paul's continued justification of his stance ("not reacting at all", 10), Megan's use of humour ("never know with the gases£", line 11) deflects from their misaligned views, and whilst they do not reach agreement, Paul shares in this laughter (line 12) which lightens the potential seriousness of the situation (Hendry, Wiggins & Anderson, 2016).…”
Section: Invoking Physical Resourcesmentioning
confidence: 99%
“…the newfound learner autonomy it places upon its students) may raise some discomfort among novice PBL tutors (e.g. the fear that students will become distracted from their group work as a result of engaging in irrelevant or off-topic discussions during the PBL sessions) amongst academics who are more accustomed to didactic methods (Hendry, Wiggins & Anderson, 2016). This can lead to premature or overly direct interventions made by inexperienced PBL tutors, which can be highly detrimental to students' own collaborative efforts (Aarnio, Lindblom-Ylänne, Nieminen & Pyörälä, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown how students more successfully meet their learning objectives through the use of PBL, but still rate this approach as secondary to standard lectures, as though they have been short-changed (Warnock and Mohammadi-Aragh 2016;Yadav, Subedi, Lundeberg, and Bunting, 2011). While the educational freedom brought by PBL may be a daunting one for teaching staff (Hendry, Wiggins, and Anderson 2016), it is this very lack of trust which fosters the 'needy' student. Instead, the willingness of educators as enablers of PBL lie at the core of its success (Azer 2005), and it is critical, therefore, that PBL is adopted from the very initial phases of the undergraduate degree.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Sam demonstrates that, whilst his own efforts were not as poorly received as his peers' ("wasn't CRAP crap"), his tutor feedback is by no means impressive ("°it wasn't great°"). This is a vulnerable point in the interaction for Sam, as he cannot ignore the blatant disparities in critique -this would impair the authenticity of his discourse -but must downplay this unavoidable superiority, or face potential ostracism from the group (Hendry, Wiggins, and Anderson 2016).…”
Section: Maintaining Average Student Identitiesmentioning
confidence: 99%
See 1 more Smart Citation